2001
DOI: 10.1128/iai.69.4.2692-2699.2001
|View full text |Cite
|
Sign up to set email alerts
|

Antimycobacterial Agent Based on mRNA Encoding Human β-Defensin 2 Enables Primary Macrophages To Restrict Growth ofMycobacterium tuberculosis

Abstract: Human macrophages are hosts for Mycobacterium tuberculosis, the causative agent of tuberculosis, which killed approximately 1.87 million people in 1997. Human alveolar macrophages do not express ␣-or ␤-defensins, broad-spectrum antimicrobial peptides which are expressed in macrophages from other species more resistant to infection with M. tuberculosis. It has been previously reported that M. tuberculosis is susceptible to killing by defensins, which may explain the difference in resistance. Defensin peptides h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 33 publications
0
45
0
2
Order By: Relevance
“…Ectopic expression of foreign peptides has suggested that peptides can be important mediators of innate immune control of bacterial pathogens. Human LL-37 augments mouse lung defense against Pseudomonas aeruginosa (34), human defensin 5 in the intestine makes mice more resistant to oral challenge with S. typhimurium (35), and human defensin expression in macrophages controls replication of pathogens such as Mycobacterium tuberculosis (36,37). Here, we show the expression, activation, and activity of an endogenous cationic peptide within macrophages, an important target cell of many significant intracellular pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic expression of foreign peptides has suggested that peptides can be important mediators of innate immune control of bacterial pathogens. Human LL-37 augments mouse lung defense against Pseudomonas aeruginosa (34), human defensin 5 in the intestine makes mice more resistant to oral challenge with S. typhimurium (35), and human defensin expression in macrophages controls replication of pathogens such as Mycobacterium tuberculosis (36,37). Here, we show the expression, activation, and activity of an endogenous cationic peptide within macrophages, an important target cell of many significant intracellular pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas Duits et al . (2002) presented data indicating the presence of two human β -defensins, hDB-1 and -2, within unactivated alveolar macrophages, Kisich et al . (2001) did not find any evidence for the presence of either α -or β -defensin in activated alveolar macrophages.…”
Section: Antibacterial Defensesmentioning
confidence: 99%
“…AMPs as therapeutics against microbes would be promising because the target of AMPs are the bacterial membrane, thus to combat AMPs the bacteria would need to redesign its membrane, which would be a "costly" solution for most species (Zasloff 2002). The possibility of alleviating bacterial infections related to cystic fibrosis through increasing physiological levels of LL-37, or re-engineering human macrophages to express beta-defensins to enhance efficacy against Mycobacterium tuberculosis have been proposed (Bals, Weiner et al 1999;Kisich, Heifets et al 2001). However, limitations as an effective therapeutic are stalled by high production costs and the susceptibility to proteolytic degradation, a mechanism which microbial pathogens secrete proteases to counter-measure the target of AMPs (Peters, Shirtliff et al 2010).…”
Section: Potential Therapeutic Value Of Ampsmentioning
confidence: 99%